Recent advances in PLLA-based biomaterial scaffolds for neural tissue engineering: Fabrication, modification, and applications - Dai, Yuan; Lu, Tingwei; Shao, Minghao; Lyu, Feizhou (Frontiers in Bioengineering and Biotechnology, 2022)
Repairing and regenerating injured neural tissue remains a worldwide challenge. Tissue engineering (TE) has been highlighted as a potential solution to provide functional substitutes for damaged organs or tissue. Among the biocompatible and biodegradable materials, poly-L-lactic-acid (PLLA) has been widely investigated in the TE field because of its tunable mechanical properties and tailorable surface functionalization. PLLA-based biomaterials can be engineered as scaffolds that mimic neural tissue extracellular matrix and modulate inflammatory responses. With technological advances, PLLA-based scaffolds can also have well-controlled three-dimensional sizes and structures to facilitate neurite extension. Furthermore, PLLA-based scaffolds have the potential to be used as drug-delivery carriers with controlled release. Moreover, owing to the good piezoelectric properties and capacity to carry conductive polymers, PLLA-based scaffolds can be combined with electrical stimulation to maintain stemness and promote axonal guidance. This mini-review summarizes and discusses the fabrication and modification techniques utilized in the PLLA-based biomaterial scaffolds for neural TE. Recent applications in peripheral nerve and spinal cord regeneration are also presented, and it is hoped that this will guide the future development of more effective and multifunctional PLLA-based nerve scaffolds.